Long COVID: The Nature of Thrombotic Sequelae Determines the Necessity of Early Anticoagulation - Wang, Chengyue; Yu, Chengyuan; Jing, Haijiao; Wu, Xiaoming; Novakovic, Valerie A.; Xie, Rujuan; Shi, Jialan (Frontiers in Cellular and Infection Microbiology, 2022)
Many discharged COVID-19 patients affected by sequelae experience reduced quality of life leading to an increased burden on the healthcare system, their families and society at large. Possible pathophysiological mechanisms of long COVID include: persistent viral replication, chronic hypoxia and inflammation. Ongoing vascular endothelial damage promotes platelet adhesion and coagulation, resulting in the impairment of various organ functions. Meanwhile, thrombosis will further aggravate vasculitis contributing to further deterioration. Thus, long COVID is essentially a thrombotic sequela. Unfortunately, there is currently no effective treatment for long COVID. This article summarizes the evidence for coagulation abnormalities in long COVID, with a focus on the pathophysiological mechanisms of thrombosis. Extracellular vesicles (EVs) released by various types of cells can carry SARS-CoV-2 through the circulation and attack distant tissues and organs. Furthermore, EVs express tissue factor and phosphatidylserine (PS) which aggravate thrombosis. Given the persistence of the virus, chronic inflammation and endothelial damage are inevitable. Pulmonary structural changes such as hypertension, embolism and fibrosis are common in long COVID. The resulting impaired lung function and chronic hypoxia again aggravates vascular inflammation and coagulation abnormalities. In this article, we also summarize recent research on antithrombotic therapy in COVID-19. There is increasing evidence that early anticoagulation can be effective in improving outcomes. In fact, persistent systemic vascular inflammation and dysfunction caused by thrombosis are key factors driving various complications of long COVID. Early prophylactic anticoagulation can prevent the release of or remove procoagulant substances, thereby protecting the vascular endothelium from damage, reducing thrombotic sequelae, and improving quality of life for long-COVID patients.